Application of Structured Problem-Based Learning Model to Improve Mathematics Learning Outcomes - Ernawati, Ernawati; Lestari, Pertiwi Indah; Suryaningsih, Ita (Universitas Muhammadiyah Mataram, 2022)
This research is motivated by the learning process that applied to the SPLDV material still uses a learning model that has not been directed to structured problems, so that learning outcomes students based on mid-semester test scores are still mostly below KKM. This study aims to determine the application of the Structured Problem-Based Learning Model in improving mathematics learning outcomes in grade VII students of Junior High School. This research is a classroom action research conducted in two cycles. Cycles I and II were held for 3 meetings, consisting of 2 meetings for the implementation of actions and one meeting for the cycle test. Data analysis technique used is descriptive statistics. The subjects of the study were class VII students, which consisted of 15 students. The instruments used are learning outcomes tests and observation sheets. The results showed that the average value of the learning test results in each cycle, namely in the first cycle the average value was 68.80 and in the second cycle the average value was 78.67. Based on these results, it can be interpreted that the learning outcomes have increased in each cycle. The results of the observations showed that the activeness and self-confidence of students in the learning process increased in each cycle. This can be seen in the average score of students who did the exercises on the blackboard in the first cycle, which was 10.00% and increasing to 30.00% in the second cycle.